La réception des Noces Chymiques d’Andreae chez Novalis - Véronique Liard (Recherches Germaniques)
Georg Philipp Friedrich von Hardenberg, better known by the name of Novalis, read alchemical writings, including The Chymical Wedding of Christian Rosencreutz from an early age. Novalis was much influenced by the mysticism of Romantic nature philosophy as well as by Jakob Böhme and he sought the philosophical stone in all its manifestations, as he told his brother in a letter of 1793. After his fiancée Sophie died, he began to idealize his love for her and the two of them were eternally bound in a mystic union. Sophie became for him the Sophia that relates the temporal world to the hereafter, and leads to self-knowledge and knowledge of the world. This paper will first examine the influence of pietism, Naturphilosophie and of Jakob Böhme before exploring how the echoes of The Chymical Wedding inform the themes of love, the union of opposites and knowledge in the poems, “The Disciples at Saïs” and “Heinrich von Ofterdingen”.